Non-calcifying Langerhans Cell Rich Variant of Calcifying Epithelial Odontogenic Tumor and Amyloid Rich Variant of Central Odontogenic Fibroma: A Unique Entity or a Spectrum? - Tseng, Chih-Huang; Lu, Pei-Hsuan; Wang, Yi-Ping; Chiang, Chun-Pin; Cheng, Yi-Shing Lisa; Chang, Julia Yu Fong (Frontiers in oral health, 2021)
Overlapping clinicopathological features of non-calcifying Langerhans cell rich variant of calcifying epithelial odontogenic tumor (NCLC-CEOT) and the amyloid rich variant of the central odontogenic fibroma (AR-COF) have been recognized recently. It is still under debate whether these two diseases are indeed one unique disease entity or belong to CEOT and COF, respectively. To clarify this issue, we have performed a literature review to compare the similarities and differences in clinicopathological features among NCLC-CEOT, AR-COF, classic CEOT, and classic COF. We aimed to investigate whether NCLC-CEOT and AR-COF might be the same and one distinctive disease entity, or a variant (or variants) of either CEOT or COF; or whether COF, NCLC-CEOT/AR-COF, and CEOT represented a histopathological spectrum of one disease. Our results indicate that NCLC-CEOT and AR-COF cases share many similar clinicopathological features. Thus, we suggest that they are the same disease entity. Due to nearly no reported recurrence of NCLC-CEOT/AR-COF cases, the conservative surgical treatment is appropriate. The NCLC-CEOT/AR-COF cases show some overlapping clinicopathological features with COF rather than the CEOT cases. However, differences in the clinicopathological features are still recognized among the NCLC-CEOT/AR-COF, COF, and CEOT cases. Future research, particularly molecular biological studies, may further elucidate their relationships and assist proper classification of the NCLC-CEOT/AR-COF cases.